2016
DOI: 10.1007/s13277-015-4719-x
|View full text |Cite
|
Sign up to set email alerts
|

The green tea polyphenol EGCG potentiates the antiproliferative activity of sunitinib in human cancer cells

Abstract: Sunitinib is a promising drug for clinical applications; however, the efficacy is reduced by the feedback activation of many signaling cascades. In this study, we investigated the ability of (-)-epigallocatechin-3-gallate (EGCG) to synergize with sunitinib and inhibit insulin receptor substrate (IRS)/mitogen-activated protein kinase (MAPK) pathway activation. MCF-7, H460, and H1975 cell lines with PIK3CA mutations were treated with sunitinib or mock treated 0-24 h and then pulsed with 0-50 μM EGCG for another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…NF-kB, its components and AP1 are the potential targets for EGCG cancer prevention [15]. EGCG was shown to enhance the antiproliferative role of sunitinib, an anticancer drug, by downregulating MAPK pathway [31]. Katiyar et al reported that treating normal human epidermal keratinocytes (NHEK) to UVB radiation induces the release of hydrogen peroxide due to oxidative stress.…”
Section: Interference With Intracellular Signaling Cascadesmentioning
confidence: 99%
See 1 more Smart Citation
“…NF-kB, its components and AP1 are the potential targets for EGCG cancer prevention [15]. EGCG was shown to enhance the antiproliferative role of sunitinib, an anticancer drug, by downregulating MAPK pathway [31]. Katiyar et al reported that treating normal human epidermal keratinocytes (NHEK) to UVB radiation induces the release of hydrogen peroxide due to oxidative stress.…”
Section: Interference With Intracellular Signaling Cascadesmentioning
confidence: 99%
“…Combination of EGCG with Sunitinib, a FDA approved drug for cancer treatment, down regulates MAPK signaling in human cancer cells. Also, it leads to greater tumor shrinkage and anti-angiogenesis in vivo as compared to sunitinib alone [31]. EGCG in combination with cisplatin has also demonstrated promising anticancerous effect on cell line [23].…”
Section: Expert Opinionmentioning
confidence: 99%
“…EGCG inhibits human prostate cancer cell (PC-3) proliferation by PI3-K-dependent signalling pathway [54]. In colon cancer EGCG induces the activation of mitogen-activated protein kinase (MAPK) [55] and Akt pathways [56]. In silico modelling approaches reveals that EGCG physically interacts with the ligand-binding domain of androgen receptor that is overexpressed in prostate cancer, leading to the inhibition of cell growth [57].…”
Section: Phytochemical Compounds and Cancermentioning
confidence: 99%
“…Recently, Scandlyn's research group has also used ER‐negative breast cancer cells to confirm that EGCG + tamoxifen/raloxifene elicited synergistic cytotoxicity and earlier enhanced apoptotic response in MDA‐MB‐231 cells, which correlated with a decrease in CYP1B1 expression and the blockage of epidermal growth factor receptor (EGFR) and mTOR signaling . Moreover, EGCG potentially synergizes with sunitinib to exert greater growth‐inhibitory effects due to its ability to suppress the insulin receptor substrate‐1 (IRS‐1)/extracellular‐signal‐regulated kinase (ERK) signaling induced by sunitinib . Collectively, evidences support approaches to augment apoptotic mechanism by targeting the pro‐survival, redox, autophagy, MDR, and epigenetic signaling pathways as rational therapeutic strategies to combat or delay the onset of chemoresistance and radioresistance in breast cancer.…”
Section: Sensitization Mechanisms Of Natural Phytochemicals In Breastmentioning
confidence: 99%